Characterization and source analysis of trace metal pollution in coastal shallow marine sediments, Wanning area, Hainan Island, China - Suimiao Wang; Xianqing Wang; Zhaofan Wang; Guangfei Guo; Liang Chen; Zanhui Huang; Dinghui Fu; Pingru Li; Xiuyu Yun (Frontiers in Marine Science, 2025)
Introduction Coastal shallow marine sediments serve as important sinks for trace metals and are crucial indicators of anthropogenic pollution. The Wanning area of Hainan Island has experienced rapid coastal development and intensified aquaculture, raising concerns about metal contamination. Methods In this study, 57 surface sediment samples were collected from the coastal shallow sea of the Wanning area. The concentrations of seven trace metals (As, Hg, Cu, Zn, Cd, Pb, and Cr) were determined. Pollution levels were evaluated using the Nemero multifactor pollution index, and source apportionment was conducted through the Positive Matrix Factorization (PMF) model. Results The average concentrations of As, Hg, Cu, Zn, Cd, Pb, and Cr were 11.40, 0.037, 11.36, 51.69, 0.10, 24.53, and 45.86 mg/kg, respectively, which generally comply with China’s Class I Marine Sediment Quality Standard. While the overall pollution level was low, localized hotspots of As, Cu, Cr, and Pb were identified. The PMF model identified four major pollution sources: aquaculture-related fish medicine (Factor 1, 17.9%), urban wastewater and farm feed (Factor 2, 30.5%), agricultural pesticide use (Factor 3, 17.3%), and maritime transportation (Factor 4, 34.3%). Discussion The results indicate that the primary contributors to trace metal pollution in the Wanning coastal area are human activities, including maritime transport, aquaculture, and agriculture. These findings highlight the need for targeted pollution control measures to ensure sustainable coastal development and marine environmental protection.

A holistic perspective on Earth system science - Yongfei Zheng; Zhengtang Guo; Nianzhi Jiao; Mu Mu; Shilong Piao; Suiyan Fu; Dinghui Yang; Maoyan Zhu (Science China Earth Sciences, 2024)

Individual and combined effects of herbicide prometryn and nitrate enrichment at environmentally relevant concentrations on photosynthesis, oxidative stress, and endosymbiont community diversity of coral Acropora hyacinthus - Qiuli Li; Dinghui Fu; Yanyu Zhou; Yuanchao Li; Liang Chen; Zhaofan Wang; Yinglang Wan; Zanhui Huang; Hongwei Zhao (Chemosphere, 2023)

Synergistic/antagonistic effects of nitrate/ammonium enrichment on fatty acid biosynthesis and translocation in coral under heat stress - Jingjing Zhang; Zanhui Huang; Yuanchao Li; Dinghui Fu; Qipei Li; Lixin Pei; Yanwei Song; Liang Chen; Hongwei Zhao; Shuh-Ji Kao (Science of The Total Environment, 2023)

Receiver function imaging of dense seismic array and deep dynamic mechanism beneath the eastern South China - Rubing Han; Dinghui Yang; Qiusheng Li; Rong Huang; Hongshuang Zhang; Jiangtao Li; Hao Chen; Zhuo Ye; Wei Fu (Science China Earth Sciences, 2023)

Modeling nutrient flows from land to rivers and seas – A review and synthesis - Xiaoyang Shan; Zhiqiang Zhu; Jiyong Ma; Dinghui Fu; Yanwei Song; Qipei Li; Zanhui Huang; Lixin Pei; Hongwei Zhao (Marine Environmental Research, 2023)